Detection and identification of a cryptic red crossbill call type in northeastern North America - Young, Matthew A.; Spahr, Timothy B.; McEnaney, Kenneth; Rhinehart, Tessa; Kahl, Stefan; Anich, Nicholas M.; Brady, Ryan; Yeany, David; Mandelbaum, Ryan (Frontiers in Bird Science, 2024)
Red crossbills (Loxia curvirostra) are the archetypal example of a taxon with high infraspecific diversity in traits including bill size and especially vocal characteristics. Currently, at least 11 different call types in North America have been recognized. Here, we demonstrate a twelfth type should be recognized. Type 12, we hypothesize, was previously overlooked as a variant call within type 10. We show with principal components analysis that the inverted “V” of Type 12 calls are consistently and demonstrably different from similar calls of birds previously categorized as Type 10 variants. Due to increasingly available recordings of crossbills gathered and archived into public databases by birders, our analyses reveal that this call type is predominantly distributed across northeastern North America. Although crossbill types do not always map to formerly described subspecies, we also argue that Type 12 likely matches the historically described L. c. neogaea, the “old Northeastern subspecies”. We argue Type 12 should be treated separately as a distinct type.